Research on Key Technologies of Performance Monitoring and Operation and Maintenance of Optical Fiber Transmission Network Driven by Big Data. (July 2020) - Zhao, Jinghong; Jin, Lei; Liu, Dong; Cheng, Shuo
Abstract: The traditional network operation and maintenance technology is that the administrator passively waits for the network fault to report and then carries on the emergency treatment. This method lacks active mechanism and has many disadvantages in dealing with network communication failure. The low timeliness of operation and maintenance reduces the reliability of network communication operation and maintenance to a certain extent, so it is particularly urgent to explore the research of network communication operation and maintenance technology driven by big data. This article describes the difference between several different transmission modes in the field of optical fiber communication, and discusses the related factors that restrict the reliability and timeliness of the optical fiber transmission network. On this basis, this paper analyses the possibility of integration of big data technology and the optical fiber network, and lists the typical application of big data technology in the optical fiber network, which provides a new thinking direction for the performance monitoring and operation maintenance of the optical fiber network.